1998
DOI: 10.1128/aem.64.1.370-375.1998
|View full text |Cite
|
Sign up to set email alerts
|

Stable-Carbon-Isotope Composition of Fatty Acids in Hydrothermal Vent Mussels Containing Methanotrophic and Thiotrophic Bacterial Endosymbionts

Abstract: Fatty acid biomarker analysis coupled with gas chromatography-isotope ratio mass spectrometry was used to confirm the presence of methanotrophic and thiotrophic bacterial endosymbionts in the tissues of a hydrothermal vent mussel (Bathymodiolussp.), collected from the Menez Gwen vent field on the mid-Atlantic ridge. Monounsaturated (n-8) fatty acids, which are diagnostic of methanotrophic bacteria, were detected in all three types of tissues examined (gill, posterior adductor, and mantle), although levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(53 citation statements)
references
References 36 publications
6
45
2
Order By: Relevance
“…The similarity to the n-7 monoenes in sulfuroxidizing bacteria, as well as the significant presence of 18:1n-7 and 20:1n-7 in the C. phaseoliformis lipids, led to the conclusion that this clam may be dependent on the above types of bacterial lipids. As for biosynthesis of the n-4 family PUFA in vent animal lipids, two reports consistently support our results: Fang et al (1993) observed a medium level of 18:3n-7,10,13 and a trace level of 22:3n-7,11,15 with high levels of monoenes and NMID in an unknown species of cold-seep mussels, and Pond et al (2002) found a small level of 18:3n-7 with significant levels of n-3 and n-6 PUFA in the vent worm Ridgea piscesae.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The similarity to the n-7 monoenes in sulfuroxidizing bacteria, as well as the significant presence of 18:1n-7 and 20:1n-7 in the C. phaseoliformis lipids, led to the conclusion that this clam may be dependent on the above types of bacterial lipids. As for biosynthesis of the n-4 family PUFA in vent animal lipids, two reports consistently support our results: Fang et al (1993) observed a medium level of 18:3n-7,10,13 and a trace level of 22:3n-7,11,15 with high levels of monoenes and NMID in an unknown species of cold-seep mussels, and Pond et al (2002) found a small level of 18:3n-7 with significant levels of n-3 and n-6 PUFA in the vent worm Ridgea piscesae.…”
Section: Resultssupporting
confidence: 88%
“…On the contrary, Pond et al (1998) suggested that a Bathymodiolus sp. might not require n-3 PUFA as the essential fatty acids.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of S-oxidizing bacteria biomarkers (C16:1x7; C18:1x7; and C20:11x7) and NMID derived from FAs (e.g. C18:3x7,10,13; C20:3x7,10,15; C20:2x7,15) and the absence of HUFA are consistent with the results of Pond et al (1998) and with other studies on animals hosting S-oxidizing endosymbiotic bacteria or feeding on them (Conway & McDowell Capuzzo 1991;Zhukova 1991;Zhukova et al 1992;Fullarton et al 1995;Pranal et al 1997). The presence of PLFA from SRB in mussels proves that they continue to be filter feeders.…”
Section: Shrimps Rimicaris Exoculatasupporting
confidence: 86%
“…Despite the fact that the mussels host S-oxidizing and methanotrophic bacteria (Fiala-Médioni et al 2002), no methanotrophic biomarker was observed in the mussel PLFA profiles. This result contradicts Pond et al (1998), in which these biomarkers were found in mussels from Lucky Strike and Menez Gwen. Type I methanotroph biomarkers (C16:1x6; and C18:1x6) were observed in other species but in smaller amounts.…”
Section: Shrimps Rimicaris Exoculatacontrasting
confidence: 70%
“…If mussels rely primarily on sedimentary detritus, their carbon and nitrogen isotopic compositions should approach those of detritusfeeding deep-sea invertebrates collected from nonvent environments (␦ 13 C ϭ Ϫ17‰, ␦ 15 N Ͼ 11‰; Van Dover and Fry 1989). The isotopic composition of organic carbon fixed by methanogenic symbionts from Lucky Strike is expected to be in the range of Ϫ20 to Ϫ28‰ (Pond et al 1998). The published value for bulk tissues collected from mussels at the Statue of Liberty site at Lucky Strike was Ϫ24‰ (Van Dover et al 1996).…”
Section: Discussionmentioning
confidence: 99%